Legal Status of Renovated Inherited Property in Divorce: Status Hukum Properti Warisan yang Direnovasi dalam Perceraian - Safitri, Sherly Mauludia; Purwaningsih, Sri Budi (Indonesian Journal of Law and Economics Review, 2025)
Background: Divorce in Indonesia often leaves disputes over property division, particularly regarding the distinction between joint property and inherited or premarital assets. Specific Background: A recurring issue is whether personal assets renovated during marriage can be considered joint property, given unclear regulations and limited case law guidance. Knowledge Gap: Current laws, including Law No. 1 of 1974 and the Compilation of Islamic Law, do not explicitly address the status of renovated inherited property, leaving courts to rely on principles of contribution and fairness. Aim: This study examines how renovated personal assets are treated in divorce cases at the Sidoarjo Religious Court and provides recommendations for legal clarity. Method: Using a normative juridical approach with statutory and case study analysis, data was collected from legislation, court decisions, and legal literature. Results: Renovations to personal property can be classified as joint property if supported by significant financial or non-financial contributions from both spouses; otherwise, they remain personal property. Evidence and proof of contribution are critical in court decisions. Novelty & Implications: The study highlights the need for clearer regulations and public awareness to prevent disputes, ensure fair asset distribution, and protect the rights of both spouses and children in divorce proceedings. Highlights: Renovated inherited assets may become joint property with documented spousal contribution. Evidence of financial and non-financial contributions is crucial in court recognition. Clearer regulations are needed to reduce disputes and ensure fairness. Keywords: Joint Property; Inherited Property; Divorce; Asset Renovation; Legal Contribution